Peningkatan Potensi Desa Loleng Melalui Program Kegiatan Kuliah Kerja Nyata Angkatan 49 Tahun 2023 - Hapizi, Amrullah Muhammad; Maghfiroh, Wasiul; Heratris, Julieta Adillah; Ningrum, Indah Setiya; Rifqi, Ahmad Nur; Alghifari, Muhammad FArhan; Alyazahra, Restika; Ahmad, Islamudin (B-Creta Publisher, 2025)
Kuliah Kerja Nyata (KKN) or community services is a process of student service to the community by conducting activities that go directly to the community. The problems that will be raised in the Community Service Program through KKN 2023 Mulawarman University are increasing public awareness about the prevention of stunting in the Loleng Village community, increasing public awareness about environmental cleanliness by holding gotong royong and increasing the creativity of loleng village children to utilise plastic waste into useful items. This community service programme aims to raise awareness of the Loleng Village community and train the creativity of Loleng Village children. The community service programme was conducted in Loleng village from 2 July to 20 August 2023 using the field method. Meetings of all group members with loleng village field assistants were conducted offline, discussions with field supervisors online, and offline implementation of work programmes. Interviews with Loleng village officials, BPD Loleng officials, and Loleng villagers aimed to gather all information about the problems in Loleng village. Discussion between group members and DPL about solutions to overcome the problems in Loleng village. Determination of work programmes that are useful to overcome the problems of Loleng village. Implementation of the work programme to solve the problems in Loleng village. Problem solving in this case has been mentioned in several points which are carried out in accordance with the agreed work programmes and implemented in Loleng Village, Kota Bangun Sub-district.